Auditoría financiera a la cuenta inventarios de la compañía productora avícola Cajamarca & Suárez "CAVICENTE" CÍA. LTDA., correspondiente al período Enero - Diciembre 2017 - Jácome Olmos, Verónica Paola (2020)
Due to the rapid expansion of the Poultry companies, the productive and financial-accountants operations, they become complex, this lead to search tools which help to detect mistakes and irregularities, in handling, execution and control of the accounting transactions. The principal objective of this project is the application of a financial audit to the inventory account in the Poultry Producer Company Cajamarca & Suarez Ltd. Co., to verify the reasonableness of the embodied information in the financial statements, focused to obtain a professional opinion, relative to the inventory management activities. For the consecution of this project the mixed approach research was used (quantitative for the conclusion of findings in the accounting accounts and the financial statements and qualitative for the opinion and report of the audit), documentary methodology and field, with a method of deductive character focused on the type of descriptive research, through the instruments like the survey and the direct observation, covered in instruments as the questioner, also of procedures and techniques of audit, which permit to collect information, check the precision and consistence of the accounting records and to emit a diagnose. I could concluded that the embodied information in the financial statements relating to the inventory accounts, does not reflect reality of the Poultry, determining a missing of $ 4.475,52, which correspond to the products inventory with $2.229,52 and shabby products $2.246,00, what happened that the utility decrease, to the register the loss of inventories of $ 38.552,24 to $ 34.076,072. It is recommended that at the end of each period to perform a financial audit to the count inventories, in order to verify the reasonableness of the presented information in the Financial Statements, since the losses affect directly to the result of the company decreasing the utility of the exercise